Integrating Technology In The Development Of Interactive Media And Learning Resources For The Digital Era - Nasir, Tatang Muh; Zulfahmi, Hikmat; Febriyadi, Fuky Ronald; Sobariah, Eneng Dewi Siti; Dharmawan, Herryanto (STAI Tuanku Tambusai, 2025)
The rapid progress of science and technology requires education to adapt through innovative and effective learning processes. Media and learning resources play a critical role in supporting students’ understanding and engagement, preventing monotonous and uninteresting learning activities. This study aims to analyze the development and functions of learning media and resources in achieving educational objectives. A qualitative method with library research was employed, focusing on the exploration of theories and best practices in media and resource utilization. The results show that well-designed media serve communicative, motivational, and perceptual functions, while learning resources must meet criteria such as practicality, flexibility, and alignment with learning objectives. The discussion emphasizes that the proper selection and application of media enhance student participation, motivation, and achievement. In conclusion, the integration of creative and adaptive learning media and resources is essential to foster effective knowledge transfer and ensure meaningful learning outcomes in modern education.